Sharia Financing Online Education: Mudhorobah, Musyarokah and Murobahah Financing - Sukma Amelia Khaerani; Fira Rakhmatika Pohan; Rauzhatu Sakinah Gustia (Journal of Islamic Economy and Community Engagement, 2023)
The word financing comes from the word "cost" which means spending funds. While financing in general is the provision of money based on an agreement or agreement between a bank and another party that requires the financed party to return the money after a certain period of time in return or profit sharing. Financing also means trust, meaning that a bank or Islamic financial institution trusts a person or company to carry out the mandate given in the form of providing funds and managing them properly, fairly and accompanied by clear ties and conditions and mutually beneficial to both parties. In Islamic financing, there are several types of financing, including: mudhorobah financing, musyarokah financing, and murobahah financing. Seeing and reviewing the increasingly advanced digital era today, it is through digital and internet that we provide service or understanding. This service has a target to provide education through social media about the differences in financing, financing users, case examples and so on in order to provide understanding for the community in moving economic factors and not forgetting activities related to Islamic law.